Land Reform and Productivity Gains with Multiple Market Imperfections - Pavel Ciaian (Economics and Econometrics Research Institute (EERI), 2007)
This paper uses a model with transaction costs and imperfect competition in the land market to analyze the efficiency and welfare effects of land reforms. We show that removing only one imperfection may have very different efficiency and welfare effects than would otherwise result from reforms that reduce both imperfections. In extreme cases, partial reforms can actually lead to welfare losses. The welfare effects are affected by the size of transaction costs, relative farm productivity and farm land demand elasticities. Partial reforms also have important income distribution effects.
Keywords: D33; D61; L12; P23; Q12; Q15; 330; Land market; transaction costs; imperfect competition; land reform; welfare effects